Trafficking in women and children in India - Nair, P. M. 1953-; Sen, Sankar. 1936-; Institute of Social Sciences (New Delhi, India); India. National Human Rights Commission; UNIFEM South Asia Regional Office, New Delhi (New Delhi : Orient Longman, 2005)
Includes case studies.
Includes bibliographical references (p. [727]-748).
Keywords: Prostitution -- India; Child prostitution -- India; Prostitution -- India -- Prevention; Child prostitution -- India -- Prevention; Prostitution -- India -- Case studies; Child prostitution -- India -- Case studies